1991
DOI: 10.1002/tea.3660280808
|View full text |Cite
|
Sign up to set email alerts
|

A method to quantify major themes of scientific literacy in science textbooks

Abstract: Science textbooks are frequently used to convey a great deal of the information that students receive in science courses. They influence how science teachers organize the curriculum and how students perceive the scientific enterprise. An overreliance on these teaching aids often results in an overemphasis on terminology and vocabulary, and presents a false impression of the nature of science. As a result of their importance, a method was developed to assess the curricular emphasis in science textbooks. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
23

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(84 citation statements)
references
References 13 publications
0
61
0
23
Order By: Relevance
“…The real natural sciences is a body of knowledge, a way of investigating, a way of thinking, and the interaction among science, technology, and society. Because that, a teacher must know the fundamental aspects of natural sciences, so they can give more complete and comprehensive image about science [1].…”
Section: Introductionmentioning
confidence: 99%
“…The real natural sciences is a body of knowledge, a way of investigating, a way of thinking, and the interaction among science, technology, and society. Because that, a teacher must know the fundamental aspects of natural sciences, so they can give more complete and comprehensive image about science [1].…”
Section: Introductionmentioning
confidence: 99%
“…It requires drawing on multiple operations whose coordinated activity enables the reader to extract, interpret, judge, and understand what has been read (Chiapetta, Sethna, & Fillman, 1991;Lemke, 1990). Far from being merely a passive and receptive subject limited to decoding, the reader takes an active role, applying knowledge and schemata as well as skills and experience to the search for meaning.…”
Section: Reading Science Texts and Writing A Summary: Some Datamentioning
confidence: 99%
“…Many authors have pointed to textbooks as powerful resources for science education (e.g., [36,37]). Textbooks may support independent learning and promote parental participation [38].…”
Section: Stse Issues In Textbooksmentioning
confidence: 99%
“…Chiappetta and colleagues [36] and Lumpe and Beck [48] analysed secondary school chemistry and biology textbooks in terms of the balance between four aspects: knowledge of science, investigative NOS, science as a way of thinking, and the interaction between science, technology, and society. The authors concluded that the textbooks focused on scientific content and its vocabulary, thus representing an unbalanced account for SL.…”
Section: Stse Issues In Textbooksmentioning
confidence: 99%